2016
DOI: 10.1038/ncomms11322
|View full text |Cite
|
Sign up to set email alerts
|

Mincle-mediated translational regulation is required for strong nitric oxide production and inflammation resolution

Abstract: In response to persistent mycobacteria infection, the host induces a granuloma, which often fails to eradicate bacteria and results in tissue damage. Diverse host receptors are required to control the formation and resolution of granuloma, but little is known concerning their regulatory interactions. Here we show that Mincle, the inducible receptor for mycobacterial cord factor, is the key switch for the transition of macrophages from cytokine expression to high nitric oxide production. In addition to its stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 66 publications
2
51
0
Order By: Relevance
“…7). First, we observed that the TLR2-driven induction of Mincle surface expression is operative and consistent with data from previous reports on TLR4 action (37,40), MyD88-dependent upregulation in response to Mycobacterium bovis BCG (42), and TLR2 activity (43). This C/EBP␤-dependent feed-forward loop enhancing the response to Mincle ligands (37) most likely accounts for the TLR2-driven G-CSF production in response to cell wall glycolipid challenge, although we acknowledge that formal proof of this mechanism would require the demonstration that the overexpression of Mincle, perhaps in association with other CLRs like Mcl, circumvents TLR2 dependence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…7). First, we observed that the TLR2-driven induction of Mincle surface expression is operative and consistent with data from previous reports on TLR4 action (37,40), MyD88-dependent upregulation in response to Mycobacterium bovis BCG (42), and TLR2 activity (43). This C/EBP␤-dependent feed-forward loop enhancing the response to Mincle ligands (37) most likely accounts for the TLR2-driven G-CSF production in response to cell wall glycolipid challenge, although we acknowledge that formal proof of this mechanism would require the demonstration that the overexpression of Mincle, perhaps in association with other CLRs like Mcl, circumvents TLR2 dependence.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the Mincle ligand TDM inhibited interleukin-12p40 (IL-12p40) production induced by the TLR2 ligand Pam3CSK4 via IL-10 production in murine macrophages (45), and Wevers et al observed that the ligation of Mincle downregulated IL-12p35 expression induced by TLR or Dectin-1 stimulation via phosphatidylinositol 3-kinase (PI3K)-protein kinase B (PKB)-dependent MDM2-mediated degradation of IRF-1 in human dendritic cells (DC) (46). An interesting mechanism for the synergistic induction of the iNOS protein by TDM and Pam3CSK4 through increased translational efficiency dependent on hypusination of the elongation factor eukaryotic initiation factor 5 (eIF5) was recently described by Lee and colleagues (43). Thus, it will be interesting to investigate the differential regulation of a wider set of inflammatory and regulatory cytokines by Mincle and TLR2 pathways after macrophages encounter corynebacteria.…”
Section: Discussionmentioning
confidence: 95%
“…Mouse neutrophils from bone marrow were separated using a Percoll density gradient, as previously described2324. Neutrophils were suspended in RPMI-1640 medium supplemented with 5% fetal calf serum.…”
Section: Methodsmentioning
confidence: 99%
“…RNA sequencing analysis was performed as previously described23. The GEO accession number for the RNA sequencing data reported in this paper is GSE70793.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation